APLIKASI PENILAIAN BERBASIS KELAS DALAM PEMBELAJARAN BAHASA INDONESIA - Supriyono Supriyono (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2019)
Application of PBK in Indonesian Language and Literature subjects, of course, it raises implications in its implementation, among others: (1) the essence and procedure of classroom-based assessment must be accepted to the teacher and clearly understood, (2) students should understand clearly what referred to class-based assessments, (3) the criteria for making decision on the results of class-based assessments should be agreed with students' parents / guardians, (4) assessments are carried out in a friendly and pleasant atmosphere, and (5) class-based assessment procedure and daily recording of student learning outcomes should be easily carried out as part of teaching and learning activities and do not have to take excessive time.